2017
DOI: 10.1108/jstpm-04-2016-0007
|View full text |Cite
|
Sign up to set email alerts
|

The Kenyan Judiciary’s Open Government Initiative: prospects and challenges

Abstract: Purpose This paper is based on an empirical study undertaken between April 2014 to December 2014 that aims to investigate the Open Government Initiative in the Kenyan Judiciary and its contribution to Judiciary transformation for enhanced justice delivery. Design/methodology/approach The paper draws from both literature and data collected from representative professionals in the Kenyan Judiciary through interviews and questionnaires. Findings The findings indicated that the Kenyan Judiciary was at its init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…Finally, the eighth major work in the OGD-focused research in an African context is conducted in the Kenyan judiciary where the authors investigated the Open Government Initiative along with the prospects and challenges of the OGD reforms (Maseh & Katuu, 2017). The underlying aim of the Kenyan Judiciary's Open Government Initiative is to promote public participation and provide better delivery of justice.…”
Section: Related Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the eighth major work in the OGD-focused research in an African context is conducted in the Kenyan judiciary where the authors investigated the Open Government Initiative along with the prospects and challenges of the OGD reforms (Maseh & Katuu, 2017). The underlying aim of the Kenyan Judiciary's Open Government Initiative is to promote public participation and provide better delivery of justice.…”
Section: Related Researchmentioning
confidence: 99%
“…In a bid to realize the goals of transparency, citizen collaboration, and administrative efficiency, governments have instituted structural and functional mechanisms for implementing OGD initiatives (De Blasio & Selva, 2016). As such, research shows that the developed countries have been more forthcoming in OGD initiatives (Serra, 2014;Wirtz & Birkmeyer, 2015;Zuiderwijk, Janssen, & Dwivedi, 2015) while the developing ones are pushing forth their OGD agenda at a slow-yet-steady pace (Afful-Dadzie & Afful-Dadzie, 2017;Maseh & Katuu, 2017;Ohemeng & Ofosu-Adarkwa, 2015;Saxena & Janssen, 2017). As such, research shows that the developed countries have been more forthcoming in OGD initiatives (Serra, 2014;Wirtz & Birkmeyer, 2015;Zuiderwijk, Janssen, & Dwivedi, 2015) while the developing ones are pushing forth their OGD agenda at a slow-yet-steady pace (Afful-Dadzie & Afful-Dadzie, 2017;Maseh & Katuu, 2017;Ohemeng & Ofosu-Adarkwa, 2015;Saxena & Janssen, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Open government information as a moderator in the relationship between public leader and public service performance. This hypothesis is supported by Hellberg and Hedstrom (2015), Ruijer and Huff (2016), Adu et al (2016), Correa et al (2017), Maseh and Katuu (2017), Janssen et al (2017).…”
Section: Methodsmentioning
confidence: 77%
“…Originality of this study shows that never been testing this investigation of public leader, open government information policy and public service performance in Indonesia. Several previous studies have found partial relationship between variables as follow: first, relationship between leadership and performance by Han et al (2010), McGurk (2010, Maddock (2011Maddock ( , 2012, Borkowski et al (2011), Parker et al (2013, Petrovsky and Ritz (2014), Brookes (2014), Reid (2014), Kellis and Ran (2015), Boddy (2016), Page (2016), Tajeddini (2016), Mathias (2017); second, role of open government information policy by Hellberg and Hedstrom (2015), Ruijer and Huff (2016), Adu et al (2016), Correa et al (2017), Maseh and Katuu (2017), Janssen et al (2017). No previous study has studied comprehensively the moderation effect of open government information policy in relationship between public leadership to public service performance, especially in Indonesia.…”
mentioning
confidence: 96%